Synthesis of Alkyne-Substituted Dihydropyrrolones as Bacterial Quorum-Sensing Inhibitors of Pseudomonas aeruginosa - Basmah Almohaywi; Tsz Tin Yu; George Iskander; Shekh Sabir; Mohan Bhadbhade; David StC. Black; Naresh Kumar (MDPI AG, 2022)
The Quorum-sensing system in Pseudomonas aeruginosa is responsible for the pathogenicity and the production of virulence factors and biofilm formation. Dihydropyrrolones were previously found to act as inhibitors of QS-dependent bacterial phenotypes. In this study, a range of dihydropyrrolone (DHP) analogues was synthesized via the lactone-lactam conversion of lactone intermediates followed by the formation of novel acetylene analogues of dihydropyrrolones from brominated dihydropyrrolones via Sonogashira coupling reactions in moderate to high yields. Upon biological testing, the most potent compounds, 39-40 and 44, showed higher bacterial quorum-sensing inhibitory (QSI) activity against P. aeruginosa reporter strain at 62.5 µM. Structure-activity relationship studies revealed that di-alkynyl substituent at the exocyclic position of DHPs possessed higher QSI activities than those of mono-alkynyl DHPs. Moreover, a hexyl-substituent at C3 of DHPs was beneficial to QSI activity while a phenyl substituent at C4 of DHPs was detrimental to QSI activity of analogues.